INKLUSI PEMBAYARAN ZAKAT DI PROVINSI RIAU - ILHAM FADHILAH PERDANA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to see the description of realization of zakat receipts, especially zakat maal in Riau Province. The realization of zakat receipts is used to see the inclusion of zakat in terms of payment by the people of Riau. This research uses quantitative descriptive approach from collecting secondary data onto various sources. This study uses the results showed that the realization of zakat receipts of Riau Province during the period 2012-2016 has increased. The receipts in zakat funds increased, directly proportional to the amount of zakat payers during the period. Nevertheless, from the realization of zakat acceptance, it can be seen that the inclusion rate of zakat payment is still low. The number of people that pay zakat is still very low when compared with the number of zakat compulsory population. More research is needed to find out the reason why.